Medidas ao combate a perdas elétricas não técnicas em áreas com severas restrições à operação de sistemas de distribuição de energia elétrica - Huback, Vanessa Barroso da Silva (2018)
One of the most critical problems that the distribution utilities face is nontechnical losses, mainly characterized by fraud and clandestine links in their network. An important part of them occurs in communities, areas that have severe restrictions on the operation (ASRO). These are places dominated by criminal groups, which are responsible for limiting the operation and supervision of the company, avoiding the adequate combat of non-technical losses. The work used the international experiences of distributors EPM, Codensa and Electricaribe (Colombia); Luz del Sur and Enel Peru (Peru); JPS (Jamaica) and Meralco (Philippines) to propose measures to reduce the non-technical losses of Brazilian distributors located in ASRO, as well as alternatives to reduce their economic losses. These include differentiated regulatory recognition for ASROs, changes in the Social Tariff, prepaid metering, social measures, electromechanical measurement in transformers, agreement with the Attorney General’s Office and publication of photos of criminals in press vehicles.